2021
DOI: 10.1088/1742-6596/1849/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

The First Principle Investigation for the Structural and Optoelectronics Properties of Tetragonal Compound CaCN2

Abstract: The present study deals with the structural, electronic and optical properties of CaCN2 ternary compound. For the computation of structural, electronic and optical properties of the CaCN2, the Perdew-Burke-Ernzerhof generalized gradient approximation (PBE-GGA) exchange correlation within the framework of density functional theory as available in Wien2k code is used. Wien2k code is based on full potential linearized augmented plane wave method. The electronic properties are investigated in terms of energy band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Other studies have been carried out on ABC 2 -type ternary compounds by replacing the copper element with other elements. For instance, Khan et al [19] investigated the structural, electronic, and optical properties of ternary CaCN 2 compound by using the DFT, where in their deduction from the study, the results showed that the compound had properties that are suitable for utilization in the photovoltaic applications. Additionally, optical properties of SrSiP 2 and CaSiP 2 compounds by using the DFT approach have been investigated [20].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have been carried out on ABC 2 -type ternary compounds by replacing the copper element with other elements. For instance, Khan et al [19] investigated the structural, electronic, and optical properties of ternary CaCN 2 compound by using the DFT, where in their deduction from the study, the results showed that the compound had properties that are suitable for utilization in the photovoltaic applications. Additionally, optical properties of SrSiP 2 and CaSiP 2 compounds by using the DFT approach have been investigated [20].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have been carried out on ternary chalcopyrite compounds by replacing the copper element with other elements. For instance; K Khan et al [13] investigated the structural, electronic, and optical properties of ternary CaCN 2 compound using DFT. Predictions from this study showed that the compound could be utilized for photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions from this study showed that the compound could be utilized for photovoltaic applications. Additionally, optical properties of SrSiP 2 and CaSiP 2 compounds using the DFT approach have been investigated [13]. Elements such as gold, silver, and aluminum among others have also been investigated as a replacement for copper for potential optoelectronic and photovoltaic applications [14]- [16].…”
Section: Introductionmentioning
confidence: 99%